Nonlinear prices, homogeneous goods, search - Atabek Atayev (ZEW - Leibniz-Zentrum für Europäische Wirtschaftsforschung, 2021)
We analyze competition on nonlinear prices in homogeneous goods markets with consumer search. In equilibrium firms offer two-part tariffs consisting of a linear price and lump-sum fee. The equilibrium production is socially efficient as the linear price of equilibrium two-part tariffs equals to the production marginal cost. Firms thus compete in lump-sum fees, which are dispersed in equilibrium. We show that sellers enjoy higher profit, whereas consumers are worse-off with two-part tariffs than with linear prices. The competition softens because with two-part tariffs firms can make effective per-consumer demand less elastic than the actual demand.
Keywords: D11; D43; D83; L13; 330; Nonlinear prices; consumer search; homogeneous goods